Plan Contracts, Territorial Pacts: Agreement for Development by Contract - De la Torre Sendoya, Luis Arturo (Universidad del Rosario, 2020)
The setting of negotiated objectives by public action contracts through instruments like contratosplan, contratos paz and now the Colombian pactos territoriales may constitute a response toterritorialize the regional development management. This text, as a result of a PhD research (2018), presents the contributions or innovations of this new figure of public action but alsothe obstacles that the experiences known today at international level reveal us.